Analisis Kelayakan Usaha Bawang Merah Gapoktan Karya Makmur Desa Pasir Kecamatan Mijen Kabupaten Demak - Ahmad Naja Abadi; Dwi Retna Sulistyawati; Gunawan Mohammad (Pusat riset dan Inovasi Nasional, 2025)
This study also highlights the importance of education and training for farmers to improve their technical skills in farming and managing their farms. Training in the use of modern agricultural technologies, such as automated fertilizing tools and efficient irrigation systems, can help farmers reduce production costs and increase yields. Furthermore, training in digital marketing can help farmers market their products more effectively through online platforms, reducing reliance on intermediaries and increasing profit margins. Furthermore, it is crucial for the government to provide support in the form of extension services and easy access to business capital. More accessible capital will enable farmers to invest in more efficient equipment and more environmentally friendly organic fertilizers. Targeted microcredit distribution to farmer groups can also accelerate the adoption of new, more productive agricultural technologies. The adoption of sustainable and environmentally friendly agricultural practices should be a long-term focus to ensure the registration of shallot farming businesses. Farmers need to be incentivized to use organic fertilizers and natural pesticides that are safer for the soil and air. Furthermore, the implementation of integrated and environmentally friendly farming systems such as agroforestry can also be an alternative to increase agricultural yields without damaging the environment. With improvements in education, training, access to capital, and the adoption of more efficient technology, shallot farming in Pasir Village can develop better and become more sustainable in the future. Furthermore, collaboration between farmer groups and local research institutions and universities can also be key to introducing new agricultural innovations.